MULTILEVEL INVERTER FED INDUCTION MOTOR DRIVE FOR POWER FACTOR CORRECTION - Balamurugam, C. R. (Institute of Advanced Engineering and Science)
Multi-level inverter fed induction motor is a single phase highly efficient motor among all. It is widely used in medium-voltage applications such as machineries, air compressors and vacuum pumps. But however this MLI fed induction motors suffered by poor quality of voltage and current due to occurrence of harmonics and poor input power factor which results high level of energy losses. This confliction is avoided by improving power factor using various power factor control methods. By improving the power factor we can get the better efficiency with reduced Total Harmonic Distortion (THD). The effectiveness of system is verified through MATLAB/SIMULINK.